2019
DOI: 10.1038/s41567-019-0484-x
|View full text |Cite
|
Sign up to set email alerts
|

Symmetry-enhanced discontinuous phase transition in a two-dimensional quantum magnet

Abstract: Theoretical studies of quantum phase transitions have suggested critical points with higher symmetries than those of the underlying Hamiltonian. Here we demonstrate a surprising emergent symmetry of the coexistence state at a strongly discontinuous phase transition between two ordered ground states. We present a quantum Monte Carlo study of a two-dimensional S = 1/2 quantum magnet hosting the antiferromagnetic (AFM) and plaquette-singlet solid (PSS) states recently detected in SrCu2(BO3)2. We observe that the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
132
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 75 publications
(150 citation statements)
references
References 56 publications
16
132
2
Order By: Relevance
“…Our work also helps shed light upon other emergent symmetries of a FOQPT. 43 In this section, we show that Eq. (1) of the main text is the most general rotationally invariant action to φγ T σ y γ and φ 4 order if assuming φ has uniform classical vacuum.…”
Section: Conclusion and Discussionmentioning
confidence: 78%
“…Our work also helps shed light upon other emergent symmetries of a FOQPT. 43 In this section, we show that Eq. (1) of the main text is the most general rotationally invariant action to φγ T σ y γ and φ 4 order if assuming φ has uniform classical vacuum.…”
Section: Conclusion and Discussionmentioning
confidence: 78%
“…In these models, the Heisenberg interaction J is supplemented by multispin correlated singlet projectors Q, which open up possibilities of designing sign-problem free Hamiltonians with the desired phase diagrams containing AFM and VBS phases. A large number of QMC studies with different variants of 2D J-Q models have been reported [48][49][50][51][52][53][54][55][56][57][58][59][60][61][62][63][64][65]. Concurrently, various discrete versions of the proposed DQC action have also been studied numerically [66][67][68], and three-dimensional classical loop [69,70] and dimer [71,72] models with arguably the same low-energy fixed points have also been studied extensively.…”
Section: A Valence-bond Solid States and Deconfined Quantum Criticalitymentioning
confidence: 99%
“…Recently, unconventional first-order transitions with emergent spherical symmetry of the order parameters were identified where no cumulant minimums are observed, which can be traced to the lack of tunneling barriers when the two order parameters can be continuously rotated into each other [36][37][38]. The results for h ≥ 0.2 in Figs.…”
Section: B Nature Of the Afm-cvbs Transitionmentioning
confidence: 99%
“…There is still some remnants of Z 4 symmetry here (a slightly diamond-like deviation from circular symmetry of the distribution), which would further diminish if we move even closer to the transition. Proper analysis of the size dependence of the distribution [36,38] would be required to draw firm conclusions, but at least it appears plausible here that the system has the emergent U(1) symmetry expected at a DQC transition.…”
Section: Fluctuations In the Vbs Phasesmentioning
confidence: 99%